On the change in bacterial size and magnetosome features for magnetospirillum magnetotacticum (MS-1) under high concentrations of zinc and nickel - Kundu, S.; Kale, A. A.; Banpurkar, Arun G.; Kulkarni, G. R.; Ogale, S. B. (Biomaterials, 2009)
The characteristic size, shape and specific alignment of magnetite crystals synthesized by magnetotactic bacteria is a highly coordinated process with precise control over magnetosome vesicle formation, uptake and transport of Fe, and magnetite biomineralization. Magnetosome membranes along with some specific membrane proteins regulate crystal nucleation and morphology of magnetite. Several previous works have indicated that the morphology of mature magnetite crystals is largely unaffected by environmental conditions, though some recent studies have shown the possibility of manipulation of the biomineralization process. In this study we have examined the effects of high concentrations of Zinc and Nickel on the growth of Magnetospirillum magnetotacticum (MS-1) and the corresponding magnetosome formation. Using various characterizations it is shown that the growth of the bacterial cells, as well as the size, shape and magnetosome chain alignment is significantly influenced in the presence of high concentrations of Zn or Ni. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biomineralization; magnetite; Magnetosome; Magnetospirillum magnetotacticum; Nickel; zinc

Controlling stoichiometry in low temperature synthesis of La0.7Sr0.3MnO3 nanoparticles - Azarifar, Ali; Yadav, P. A.; Chawla, A. K.; Jog, Jyoti Prakash; Patil, S. I.; Chandra, Ramesh; Ogale, S. B. (Advanced Science Letters, 2011)
Nanoparticles of complex oxides (<20 nm) are desirable for several applications in view of the diverse range of physical properties of such oxides. However the simultaneous presence of multiple cation precursors makes the corresponding chemical synthesis non-trivial with possible intermediate evolution of secondary phases. Such phases could react at high temperatures to form the desired stoichiometry, but this process is diffusion limited and can lead to larger particles. In this work we examine the role of three different reaction and growth controlling additives, namely dextran, citric acid and hexamine, on the synthesis of the well known colossal magneto-resistive (CMR) manganite La0.7Sr0.3MnO3. We demonstrate that phase evolutions differ significantly in the three cases, and the physical properties of the products also differ dramatically. Only dextran is shown to yield the desired phase with faceted nanoparticles at as low a temperature as 600 degrees C. A high saturation moment of similar to 47 emu/gm is realized at 10 K with a good square hysteresis loop. In 650 degrees C annealed sample, room temperature magnetization of similar to 15 emu/gm was obtained, which brings the nanoparticles in the applicability domain.
Keywords: Citric acid; Complex Oxide; Dextran; Hexamine; hydrothermal